Analysis of the spore germination mechanisms of Clostridium difficile - Burns, David Alexander (2011)
Clostridium difficile is the leading cause of hospital acquired diarrhoea and a major burden to healthcare services worldwide. Endospore production plays a pivotal role in infection and disease transmission, but in order to cause disease these spores must germinate and return to vegetative cell growth. Therefore, knowledge of spore germination is important and may have direct applications in future disease prevention. Germination has been well studied in Bacillus and in some clostridia, but the mechanisms of C. difficile spore germination remain unclear. Apparent homologues of genes important for germination in other spore formers have been identified in the C. difficile genome and ClosTron technology was used to inactivate homologues of sleC, cspA, cspB and cspC (Clostridium perfringens) and cwlJ, sleB and cwlD (Bacillus subtilis) in both C. difficile 630Δerm and a BI/NAP1/027 isolate (a ‘hypervirulent’ type associated with outbreaks of increased disease severity). Using a combination of several different assays to study these mutants in detail, a number of the identified target genes appear to be essential for germination and outgrowth of C. difficile spores. This is the first report of using reverse genetics to study the germination of C. difficile spores and the first gene characterisation by mutagenesis in a BI/NAP1/027 isolate of C. difficile. Furthermore, this study uncovered evidence of significant variation in the sporulation and germination characteristics of different C. difficile strains, but this variation did not appear to be type-associated.